ANALYSIS OF CRITICAL THINKING SKILLS ON FLAT BUILDING MATERIALS USING VAN HIELE'S THEORY IN ELEMENTARY SCHOOL - Moh. Zakki Susanto; Martha Sukma Wijaya; Nabila Salima Azzahro; Cholifah Tur Rosidah; Susi Hermin Rusminati (Media Inovasi Pendidikan dan Publikasi, 2023)
Learning mathematics has a special role in forming students' thinking concepts. The level of student thinking refers to the ability of students to analyze and return their own thinking concepts to mathematical problems. One of the materials in mathematics is geometry, which is a branch of mathematics that seeks to relate geometric elements and concepts in everyday life. Referring to Van Hiele's learning theory, the solution to solving the problem is with a learning method based on the level of students' understanding of geometry in flat shape material which is divided into five learning stages. This research is intended to find out and understand what are the obstacles students experience in the process of learning geometry on flat shape materials and offer the best solutions for their completion. By using the literature study research method, we are able to collect factual information about the topics we will discuss, namely analyzing critical thinking skills on flat shape materials and solving them according to Van Hiele's theory. The results of this study indicate that by using Van Hiele's 5 stages, learning can be carried out well without any problems and can improve students' critical thinking skills.